UMP Squash Reservation System using Lighting Control - Mahdi Hishamuddin, Abdul Aziz; Junaida, Sulaiman (2016)
University Malaysia Pahang (UMP) sports center is the main placed for the students and staff for doing their activities, such as playing squash, badminton, football and basketball. The UMP sports center provides two squash courts to the student and staff to use. They must make a reservation and pay with affordable price to use the court. Users must pay for RM1.00 (Student) and RM 5.00 (Staff) for one hour.